2008
DOI: 10.1093/ejechocard/jen134
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional strain to assess regional left and right ventricular longitudinal function in 100 normal foetuses

Abstract: This study demonstrated that 2D-S is a feasible and reproducible approach to assess regional ventricular function in the foetal heart, ready for the clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 10 publications
5
66
0
1
Order By: Relevance
“…233,[308][309][310][311][312][313][314][315][316][317][318][319] Several of these studies have applied 2D speckle tracking echocardiography to the normal midgestation to late-gestation fetus for the assessment of longitudinal mechanics, although only 1 study to date has also addressed circumferential strain. 318 In general, feasibility is reasonable, although some studies have reported up to 20% to 30% interobserver variability.…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 99%
“…233,[308][309][310][311][312][313][314][315][316][317][318][319] Several of these studies have applied 2D speckle tracking echocardiography to the normal midgestation to late-gestation fetus for the assessment of longitudinal mechanics, although only 1 study to date has also addressed circumferential strain. 318 In general, feasibility is reasonable, although some studies have reported up to 20% to 30% interobserver variability.…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 99%
“…24 At the present time, fetal studies using 2D CPA have focused on the 4-chamber view, analyzing either the left or right ventricular chambers. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Therefore, the nomenclature for segmental analysis has to be reconsidered to include the ventricular basal lateral wall and septum, the mid lateral wall and septum, and the apical lateral wall and septum for both right and left ventricles (Figure 8). When the heart is oriented with the apex in the oblique or perpendicular positions, the full thickness of the walls and septum may be imaged and the endocardium clearly delineated.…”
Section: Increasing the Size Of The Imagementioning
confidence: 99%
“…25 Two-dimensional speckle-tracking analysis of the fetal heart has been of interest to investigators since 2005. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Although there have been differences in equipment and findings, this technology has the potential for broad application in fetal medicine. Deformation analysis has been evaluated in fetuses with twin-twin transfusion syndrome, intrauterine growth restriction, maternal diabetes, as well as other fetal conditions.…”
mentioning
confidence: 99%
“…Many other works [2,[14][15][16][17][18][19] have related to tracking quality indices that have been employed in order to decide whether to include or exclude strain measurements. The commercial vendors usually provide tracking quality indices that state a scoring of "acceptable" or "non-acceptable" segmental strain measurements, with the option of manual corrections.…”
Section: Introductionmentioning
confidence: 99%